COMPARATIVE STUDY OF FIXED DOSE COMBINATION OF OLMESARTAN +AMLODIPINE VS TELMESARTAN+METOPROLOL IN STAGE I AND STAGE II HYPERTENSIVE PATIENTS AND ALSO CHECK THEIR EFFECTS ON LIPID METABOLISM - Shah, Virag Shekhar; Dighore, Pitambar Nilkanth; Patel, Hetal Atulbhai; Upasani, Sughosh Vishweshwer (Asian Journal of Pharmaceutical and Clinical Research, 2013)
ABSTRACT: Objectives - Hypertension is the second most severe problem after diabetes in India for the mortality rate. So the primary goal to reduce the mortality is to achieving targeted blood pressure in an individual. Hypertension guidelines recommend the use of 2 agents having complementary mechanisms of action when >1 agent is needed to achieve blood pressure (BP) goals. The objectives of this study are to compare the effect of combination on BP, Lipid Profile, and also to check the safety of both combinations. Methods- This is 16 week open label, study, in which total 70 patient were enrolled. The study was carried out at outpatient department of Indira Gandhi Memorial Hospital Shirpur, Dist- dhule. We include patients which are newly diagnosed to hypertension. Permission from Institutional Human Ethical Committee was obtained. Results- combination therapies shows greater effects on lowering blood pressure than individual monotherapies. In our study we found group II combination shows greater effect than group I combination. The mean BP reduction was found to be ± 31.9/ 13.05 in group I, while in group II ±33.24/15.59 mmHg in group II from baseline after three months follow-up for systolic and diastolic respectively. While comparing lipid profile again Group II shows better results than Group I. Conclusion- These finding shows that the group II shows greater efficacy than group I in all parameter evaluated. The finding also shows that both the combinations are safe and efficacious. Key words- Hypertension, Olmesartan, Amlodipine, Telmesartan, Metoprolol, combination therapy, Lipid Profile, Fixed Dose Combination.